Reliability and validity of the Serbian version of Children's Dental Fear Questionnaire - Lalić, Maja Radiša; Aleksić, Ema; Milić, Jasmina; Malešević, Adam; Jovičić, Bojan (Vojnosanitetski pregled, 2015)
Background/Aim. Dental anxiety leads to avoidance of dental treatment and could lead to impaired oral health. The aim of this study was to determine the reliability of the Serbian version of Children’s Fear Survey Schedule Dental Subscale (CFSS-DS) and the relations between dental anxiety and oral health status in a sample of Serbian schoolchildren. Methods. The CFSS-DS scale was translated into Serbian and administered to 231 (12-year old) patients of the Pediatric Dental Department, Public Health Center Čukarica, Belgrade. The number of healthy, decayed, missing and filled teeth (DMFT score) in children was determined by a clinical exam. Results. The average CFSS-DS score was 26.47 ± 10.33. The girls reported higher anxiety than the boys (p
Keywords: child; dental anxiety; questionnaires; serbia